Functional brain networks associated with the urge for action : Implications for pathological urge - Zouki, Jade-Jocelyne; Eapen, Valsamma; Efron, Daryl; Maxwell, Amanda; Corp, Daniel T.; Silk, Timothy J. (Elsevier, 2025)
Tics in Tourette syndrome (TS) are often preceded by sensory urges that drive the motor and vocal symptoms. Many everyday physiological behaviors are associated with sensory phenomena experienced as an urge for action, which may provide insight into the neural correlates of this pathological urge to tic that remains elusive. This study aimed to identify a brain network common to distinct physiological behaviors in healthy individuals, and in turn, examine whether this network converges with a network we previously localized in TS, using novel ‘coordinate network mapping’ methods. Systematic searches were conducted to identify functional neuroimaging studies reporting correlates of the urge to micturate, swallow, blink, or cough. Using activation likelihood estimation meta-analysis, we identified an ‘urge network’ common to these physiological behaviors, involving the bilateral insula/claustrum/inferior frontal gyrus/supplementary motor area, mid-/anterior- cingulate cortex (ACC), right postcentral gyrus, and left thalamus/precentral gyrus. Similarity between the urge and TS networks was identified in the bilateral insula, ACC, and left thalamus/claustrum. The potential role of the insula/ACC as nodes in the network for bodily representations of the urge to tic are discussed.